2014
DOI: 10.1021/ie501124s
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Identification and Control of an Air Preheating Furnace of a Pneumatic Conveying and Drying Process

Abstract: The present work uses a scale down industrial pneumatic conveying and drying system in order to develop control-oriented models and suitable robust control strategies for the air preheating furnace of the system. A better control system has been achieved by utilizing the benefits of integrating first principle models, system identification techniques and parametric robust control methods. Though these processes are widely used in drying and transmission of different food, pharmaceutical and industrial products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Pneumatic dryers are a conventional drying method that offers the benefits of a simple structure and low cost, making them widely used in various industrial applications. , Previous studies have shown that gas and particle flow rates have a significant impact on the performance of pneumatic dryers, particularly when used as a predryer in a PVC suspension production line . Researchers have also developed dimensionless correlations to describe particle velocity and acceleration length in pneumatic conveying .…”
Section: Introductionmentioning
confidence: 99%
“…Pneumatic dryers are a conventional drying method that offers the benefits of a simple structure and low cost, making them widely used in various industrial applications. , Previous studies have shown that gas and particle flow rates have a significant impact on the performance of pneumatic dryers, particularly when used as a predryer in a PVC suspension production line . Researchers have also developed dimensionless correlations to describe particle velocity and acceleration length in pneumatic conveying .…”
Section: Introductionmentioning
confidence: 99%
“…Thanawat proposed a genetic algorithm to establish a walking furnace bottom style mathematical model. This method allows estimating the parameters of the mathematical model of a heating furnace based on the measured temperatures of each heating zone of the furnace [7].ZHANG C proposed the application of model predictive control algorithm to electric heating control [8].Satpati B used a continuous time (CT) data-driven model identification technique based on the simplified fine instrumental variable (SRIV) method to identify model parameters based on the desired structure [9].…”
Section: Introductionmentioning
confidence: 99%